Co-writing, Co-knowing. Transforming Epistemologies - Melissa Burchard; Karin Peterson; Alice Weldon; Leah Mathews; Amy Lanou (Praktyka Teoretyczna, 2013)
Our article offers a vision of how collaborative processes of knowledge-making in an interdisciplinary faculty writing group can transform professional lives of isolation into ones that flourish. Central to our co-creation of knowledge are the practice of storytelling in a critical self-reflective manner and the elements of commitment, connection and relationship. Together we have found that these elements provide basic strategies for managing the isolation that would otherwise be a significant force in our working lives. Our commitment is epistemological and moral, as we commit to knowledge-making, but also to each other as individuals and as moral agents, to our values, and to bringing our values into our work. Learning about ourselves together can enhance our sense of identity and our ability to navigate limits and boundaries. Through supportive, intentional and reflective collaboration, we re-vision knowledge-making as fundamentally social and relational, and theorizing as grounded in the specificity of narratives of shared, lived experience.